Effects of dietary glycerol monolaurate supplementation on milk production and methane emissions in Holstein dairy cows - R.L. Culbertson; P. Uzun; N. Seneviratne; A.B. Portela Fontoura; A.N. Davis; J.W. McFadden (JDS Communications)
Glycerol monolaurate (GML) has antimicrobial and anti-inflammatory properties in nonruminants. In vitro, GML reduces methane (CH4) production; however, the effects of dietary GML supplementation on milk production and CH4 emissions have not been evaluated in dairy cattle. In a completely randomized design, 42 mid-lactation Holstein cows (3.10 ± 1.08 lactations; 40.0 ± 6.65 kg milk/d) were acclimated to a tiestall barn for 3 wk and assigned to 1 of 3 treatments (n = 14/treatment): unsupplemented (CON), low-dose GML (50 g/d; LD), or high-dose GML (150 g/d; HD) for a 21-d experimental period. Cows were fed a base diet composed of corn silage, grass haylage, and concentrates and milked thrice daily. During the final week of acclimation and the experimental period, milk was sampled consecutively for 9 milkings/week. Methane, carbon dioxide (CO2), and hydrogen (H2) gas measurements were collected 3 times per day over 4 d (12 samples/cow) using the GreenFeed system (C-Lock Inc., Rapid City, SD). The statistical model included fixed effects of treatment, day, and treatment × day as well as random effect of cow. Planned contrasts to compare CON versus LD and CON versus HD were employed. Dry matter intakes, milk yields, and ECM yields were not affected by treatment. However, HD cows tended to produce more 3.5% FCM, relative to CON (46.6 vs. 44.8 kg/d). Milk fat contents (4.22% vs. 4.01%) and yields (1.76 vs. 1.62 kg/d) were greater in HD, relative to CON. The LD and HD cows had higher contents and yields of de novo fatty acids, including lauric acid, relative to CON. Milk protein contents were lower for HD cows, relative to CON (3.42% vs. 3.49%). Milk protein yields were lower in LD and HD, relative to CON (1.46, 1.46, and 1.52 kg/d, respectively). Milk lactose contents and yields were not affected by treatment. Cows provided the HD treatment tended to have improved feed efficiency (i.e., kg of milk, 3.5% FCM, and ECM per unit of DMI), relative to CON. Methane production, intensity, and yield, and CO2 and H2 production were not affected. We conclude that dietary GML supplementation altered milk production; however, GML feeding at the levels used in this study did not modify enteric CH4 production, intensity, or yield in dairy cattle.